Design and construction of a Boost type dc / dc converter with adjustable PWM - Marulanda Durango, Jesser James; Ordoñez, Jhon Jairo; Mosquera Machado, Luis Fernando (Scientia et Technica, 2017)
For the design of the experimental prototype of the boost converter with adjustable PWM, this project was divided into 4 stages, the first stage of a study modules oriented teaching power converters in the second design of the converter is performed is performed in the third stage the experimental module (construction adjustable PWM is constructed, whose purpose is to make changes in real time on the circuit, frequency and variable duty cycle, construction of the power circuit with the specifications given finally designs converter housing) in the fourth stage the theoretical and practical module values are analyzed.